Investigating Effect of Coherent Emission Length on Pion Interferometry in High-Energy Collisions Using a Multiphase Transport Model - Wang, Shi-Yao; Zhang, Wei-Ning (Frontiers in Physics, 2022)
In this paper, the two-pion Hanbury Brown-Twiss correlation functions for a partially coherent source constructed with the emission points and momenta of the identical pions generated by a multi-phase transport model are studied. A coherent emission length is introduced, the effects of which on the two-pion interferometry results in central Au-Au collisions at s_NN=200 GeV, central Pb-Pb collisions at s_NN=2.76 TeV, and p-p collisions at s=13 TeV are investigated. It is found that the effect of coherent emission length reduces the two-pion correlation functions in the nucleus-nucleus collisions, leading to an average decrease of the chaoticity parameter by approximately 15% in the high-transverse-momentum range. However, the influence of coherent emission length on the two-pion correlation functions in the p-p collisions is small, while the effect of coherent emission length on the chaoticity parameter is almost independent of the transverse momentum of pion pair in the p-p collisions.